Hubungan Pendidikan, Dukungan Suami dan Dukungan Tenaga Kesehatan dengan Kepatuhan Pemeriksaan K4 di Puskesmas Sukarami Palembang Tahun 2021 - Karellita Indah Khairumnisa; Eka Rahmawati; Putu Lusita Nati Indriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Antenatal Care (ANC) visits are significantly implemented as soon as possible in order to examine the women’s physical and mental health so that they are readily able to face labor. According to the Wold Health Organization (WHO), the Maternal Mortality Rate is still high. Around 810 women died due to complication related to pregnancy or labor all around the world each day, The objective of the study is to know the relationship of education, husbands’supports and health workers’ supports with K4 examination adherence at Public Health Center Sukarami Palembang in 2021. The research design used the Analytical Survey with the Cross Sectional approach. The population in the research consisted of the third trimester pregnant women tho came to check their pregmancy in June - August at Public Health Center  Sukarami, Palembang, of which the number was 174 pregnant women. The sampling technique in the research was done by the Purposive Sampling with the number of samples containing 64 respondents. The data collection used the questionnaire forms. The data analysis used the univariate analysis and bivariate analysis by means of Chi Square test. The research result showed the relationship of education (p value = 0,000), husbands’supports ( p value = 0,0000), and health workers’ supports (p value = 0,000) with K4 Examination Adherence at Public Health Center Sukarami, Palembang in 2021. It is expected that this research result can be a description for the Puskesmas party to better increase the pregnant women visits at its working area by giving any information to the pregnant women about pregnancy examination.